1982
DOI: 10.1029/rs017i006p01393
|View full text |Cite
|
Sign up to set email alerts
|

An improved model for diversity gain on earth‐space propagation paths

Abstract: An empirical model has been generated to estimate diversity gain on earth‐space propagation paths as a function of earth terminal separation distance, link frequency, elevation angle, and angle between the baseline and the path azimuth. This analysis utilized 34 diversity experiments which have been conducted in Canada, England, Japan, and the United States during the past decade. The resulting model reproduces the entire experimental data set with an rms error of 0.73 dB. The separation distance dominates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 6 publications
1
58
0
2
Order By: Relevance
“…The prediction capabilities of both models are tested against the ITU-R 618-10 for rain attenuation prediction, and Hodge, Panagopoulos and Nagaraja models for site diversity gain prediction are shown in Sect. 5 (Panagopoulos, 2005;Hodge, 1982;ITU-R, 2009;Nagaraja and Otung, 2012). Finally, Sect.…”
Section: F a Semire Et Al: Modeling Of Rain Attenuation And Site Dmentioning
confidence: 99%
See 2 more Smart Citations
“…The prediction capabilities of both models are tested against the ITU-R 618-10 for rain attenuation prediction, and Hodge, Panagopoulos and Nagaraja models for site diversity gain prediction are shown in Sect. 5 (Panagopoulos, 2005;Hodge, 1982;ITU-R, 2009;Nagaraja and Otung, 2012). Finally, Sect.…”
Section: F a Semire Et Al: Modeling Of Rain Attenuation And Site Dmentioning
confidence: 99%
“…Diversity gain is the improvement in the system margin at a given reliability level which results from the use of path diversity. Models for prediction of rain attenuation and site diversity performance are categorized into two major classes: (1) regression models based on long-term rain attenuation and site diversity statistics (Panagopoulos et al, 2005;Hodge, 1982;ITU-R, 2009;Moupfouma, 1984;Dissanayake et al, 1997;Mandeep et al, 2006) and (2) physical models based on the solution of wave equations for a medium with raindrops which employs lognormal distribution of rain rate and rain attenuation in prediction of joint probability of dual site diversity (Bosisio and Riva, 1998;Mass, 1987;Capsoni and Matricciani, 1985;Crane and Shieh, 1989;Matricciani, 1994).…”
Section: F a Semire Et Al: Modeling Of Rain Attenuation And Site Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the single site prediction and the diversity model fit quite well for the 2 years of measurement. For comparison of diversity prediction it is more useful to plot the equipropable diversity gain, defined as the difference (in dB) between the attenuation for a single terminal and the joint (diversity) attenuation at a fixed probability [17]. In Fig.…”
Section: Diversity Gain and Comparison With Modelsmentioning
confidence: 99%
“…Hodge [30,31] has shown that the diversity gain can be computed from a given attenuation, A and the separation distance, d:…”
Section: Site Diversity Planningmentioning
confidence: 99%